Evaluasi Kualitas Informasi Situs WEB Pemerintahan Kabupaten Toba - Gracia, Alfiany Devi; Prima, Yunita; Priyatna, Centurion Chandratama (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to evaluate the quality of information on the official website of the Toba Regency Government. Using a descriptive qualitative approach, the study assesses the accuracy and completeness of the information provided. The results show that overall, the accuracy of information on the official website of the Toba Regency Government is fairly good, but it requires periodic rechecking and improvement. Some identified shortcomings include the insecurity of certain websites, the presence of empty pages without information or data, and suboptimal navigation options that lead visitors back to the homepage. Additionally, the lack of information updates is a significant issue, considering the importance of providing up-to-date information to the public about activities and recent developments. Therefore, it is recommended that efforts for regular improvement and updates be undertaken to enhance the quality and reliability of the Toba Regency Government's website.